Finite-state machine for embedded systems - Galan, Peter (Control Engineering, 2021)
Finite-state machine, FSM, embedded system programming One definition of a finite-state machine (FSM) is that FSM is a mathematical model of a sequence of events and actions describing a certain (logical) process. In the engineering practice you can find countless such processes, starting with a very simple process of controlling an electric motor by a couple of push buttons, and ending with a very complex FSM system monitoring a very complicated manufacturing process or a space shuttle. Each EDFA uses one or two (for a more common, two-stage EDFA) laser pumps, which provide the energy to a coil of a special optical fiber placed inside EDFA. [...]it copies the row's nextState to the stt's currentState.